2021
DOI: 10.1080/07853890.2021.1916070
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers in acute myocardial infarction and the correlation with the severity of coronary heart disease

Abstract: Introduction: The inflammatory hypothesis of atherosclerosis is appealing in acute coronary syndromes, but the dynamics and precise role are not established.Objectives: The study investigates the levels of C reactive protein (CRP), interleukin 1b (IL-1b) and stromal-derived factor 1a (SDF-1a) at the time of acute myocardial infarction (AMI) and at 1 and 6 months afterwards, compared with a control group. Results: In the acute phase of AMI, CRP and SDF-1a were significantly higher, while IL-1b showed lower leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 30 publications
1
11
2
Order By: Relevance
“…Cardiovascular diseases account for more than 30% of deaths from noncommunicable diseases worldwide. Hyperlipidemia is the primary risk factor for atherosclerosis, which is the pathological basis for coronary heart disease, cerebral thrombosis, and other ischemic heart and brain diseases. , The risk of hyperlipidemia increases with age or with long-term irregular and unhealthy eating habits. Hyperlipidemia, as a common metabolic disease, can lead to cardiovascular, liver, and other “age-related” diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases account for more than 30% of deaths from noncommunicable diseases worldwide. Hyperlipidemia is the primary risk factor for atherosclerosis, which is the pathological basis for coronary heart disease, cerebral thrombosis, and other ischemic heart and brain diseases. , The risk of hyperlipidemia increases with age or with long-term irregular and unhealthy eating habits. Hyperlipidemia, as a common metabolic disease, can lead to cardiovascular, liver, and other “age-related” diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Tajfard et al reported that elevated serum hs-CRP levels are significantly associated with the angiographic severity of CAD [31]. Oprescu et al have also found that CRP positively correlates with coronary stenosis severity (r = 0.3, P = 0.05) [32]. However, the nonconventional RFs, such as lipoprotein (a) and homocysteine, were not associated with the severity of CAD in our study, possibly because of differences among participants involved in our study compared with prior studies.…”
Section: Discussionmentioning
confidence: 98%
“…5 Myocardial infarction is usually diagnosed clinically or by studying the electrical activity of the heart, but still, the role of biochemical markers is established and used in clinical practice. 6 Habib et al 2011 conducted a study to compare different bio-chemical markers in STEMI and NSTEMI. They revealed that levels of CRP were found more raised in patients with MI with ST-segment elevation than those who did not show ST-segment elevation at electrocardiogram.…”
Section: Introductionmentioning
confidence: 99%